Lung Cancer Detection and Classification using Machine Learning Algorithm (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Main Objective of this research paper is to find out the early stage of lung cancer and explore the accuracy levels ofvarious machine learning algorithms. After a systematic literature study, we found out that some classifiers have low accuracy and some arehigher accuracy but difficult to reached nearer of 100%. Low accuracy and high implementation cost due to improper dealing wi th DICOMimages. For medical image processing many different types of images are used but Computer Tomography (CT) scans are generallypreferred because of less noise. Deep learning is proven to be the best method for medical image processing, lung nodule detection andclassification, feature extraction and lung cancer stage prediction. In the first stage of this system used image processing techniques toextract lung regions. The segmentation is done using K Means. The features are extracted from the segmented images and the classificationare done using various machine learning algorithm. The performances of the proposed approaches are evaluated based on their accuracy,sensitivity, specificity and classification time.